"You Are so Smart!": The Role of Giftedness, Parental Feedback, and Parents' Mindsets in Predicting Students' Mindsets. (July 2022) - Boncquet, Michiel; Lavrijsen, Jeroen; Vansteenkiste, Maarten; Verschueren, Karine; Soenens, Bart
Although it has been hypothesized that gifted students are at risk for adopting a fixed mind-set, research revealed inconsistent results. We aimed to clarify this by differentiating between two operationalizations of giftedness (high cognitive ability and formal identification as gifted) and how these relate to students' beliefs about intelligence and effort. Also, we examined the role of parental antecedents on students' beliefs. Participants were 3, 329 seventh-grade students and their parents. Only being labeled as gifted was related to adopting a fixed mind-set. Regarding parental antecedents, parents' intelligence and effort beliefs were related to students' corresponding beliefs. Furthermore, parental feedback was associated with students' beliefs, which was most pronounced when student-reports of feedback were used. In particular, person-oriented feedback related positively to a fixed mind-set and negatively to students' appreciation of the role of effort in academic performance, while process-oriented feedback showed the opposite pattern. Theoretical and practical implications are discussed.